2019
DOI: 10.3390/app9194085
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Electromagnetic Interactions and Electron Transfer in Ga Nanoparticle–Graphene–Metal Substrate Sandwich Systems

Abstract: Plasmonic metal nanoparticle (NP)–graphene (G) systems are of great interest due their potential role in applications as surface-enhanced spectroscopies, enhanced photodetection, and photocatalysis. Most of these studies have been performed using noble metal NPs of silver and gold. However, recent studies have demonstrated that the noble metal–graphene interaction leads to strong distortions of the graphene sheet. In order to overcome this issue, we propose the use of Ga NPs that, due to their weak interaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…While most of the work related to SERS is focusing on the more practical aspect of reaching as high as possible enhancement ratios, a better fundamental understanding of the processes remains to be achieved. Although the interplay of different mechanisms is difficult to be explained using simple theories, mostly due to the considerable diversity of the results obtained by different research groups, both experimentalists and theorists are converging to an agreement that the enhancement mainly arises from two contributions, the electromagnetic (EME) and electronic or chemical (CE) enhancement mechanisms. It has been confirmed that surface plasmon polaritons (SPPs) play a crucial role by drastically increasing the intensity of the local electromagnetic field of the exciting laser light as well as the inelastically scattered Raman signal for the EME to be observed. In addition to the EME, which due to its nature should be independent of the molecules under investigation, there is clear evidence that there is a second enhancement mechanism, which works independently and contributes to a signal enhancement in parallel to the EME.…”
Section: Introductionmentioning
confidence: 99%
“…While most of the work related to SERS is focusing on the more practical aspect of reaching as high as possible enhancement ratios, a better fundamental understanding of the processes remains to be achieved. Although the interplay of different mechanisms is difficult to be explained using simple theories, mostly due to the considerable diversity of the results obtained by different research groups, both experimentalists and theorists are converging to an agreement that the enhancement mainly arises from two contributions, the electromagnetic (EME) and electronic or chemical (CE) enhancement mechanisms. It has been confirmed that surface plasmon polaritons (SPPs) play a crucial role by drastically increasing the intensity of the local electromagnetic field of the exciting laser light as well as the inelastically scattered Raman signal for the EME to be observed. In addition to the EME, which due to its nature should be independent of the molecules under investigation, there is clear evidence that there is a second enhancement mechanism, which works independently and contributes to a signal enhancement in parallel to the EME.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the surface conductivity matrix of magnetized graphene is applied for the infinitesimally thin graphene sheet. The localized surface plasmon resonance in the graphene-based sandwich structure is demonstrated using the FDTD simulation and provides the strong interaction of graphene with metals having higher EM wave confinement [89].…”
Section: Electromagnetic Interaction and Computational Modeling Of Grmentioning
confidence: 99%
“…Nitrides are used as alternative materials as these are refractory materials, have high electron conductivity, mobility, high melting points and also CMOS compatibility. These properties make nitrides as good candidates in optical sensors, heat-assisted recording magnetic (HAMR) [8][9][10][11][12]. As both the imaginary part (loss) and the real part of the permittivity are critical factors to consider when developing alternative plasmonic materials, It is shown by comparing permittivities of Au, Ag, TiN and ZrN that nitrides are best plasmonics in infrared region.…”
Section: Introductionmentioning
confidence: 99%